PENANAMAN NILAI PENDIDIKAN KARAKTER RELIGIUS PADA REMAJA MASJID BAITUL IZZA DESA TENGGULI KECAMATAN SAJAD TAHUN 2020 - Patimah; Mujahidin; Asyruni Multahada (CV. ADIBA AISHA AMIRA, 2024)
The aim of this research is to describe and find out about: 1) instilling religious character education values ​​in Baitul Izza mosque teenagers, 2) strategies for instilling religious character education values ​​in Baitul Izza mosque teenagers, 3) methods of instilling religious character education values ​​in Baitul mosque teenagers Izza. This research uses a qualitative approach and the type of research used is phenomenology. The data collection techniques used were observation, interviews and documentation. Then the data analysis techniques used in this research are data reduction, data display/data presentation and drawing conclusions. Meanwhile, the technique for checking the validity of the researcher's data uses: triangulation and member check. The results of this research show that: 1) instilling religious character education values ​​in Baitul Izza mosque teenagers are a) honest values, b) trustworthy values, c) patient values, d) sincere values, e) polite values, f) responsible values answer, g) tolerance value. 2) strategy for instilling religious character education values ​​in Baitul Izza mosque teenagers is a) strategy for choosing the right time, b) strategy for speaking according to what is being done, c) strategy for taming the heart, d) strategy for preparing facilities and infrastructure. 3) the method of instilling religious character education values ​​in Baitul Izza mosque teenagers is a) the personal approach method, b) the lecture method, c) the example method, d) the habituation method, e) the Advice method.